PENINGKATAN LITERASI CODING MELALUI PEMBELAJARAN BERBANTUAN AI SEBAGAI MEDIA INOVATIF - Safrizal, Andrian Syahputra, Lili Tanti, Ramadani, Rabiana Saragih, Suci Sanjaya (PT.JNDI, JURNAL BIMA, 2026)
The development of digital technology and artificial intelligence (AI) demands innovation in the learning process, particularly in strengthening digital literacy and the computational thinking skills of teachers as learning designers. However, many educational institutions still face limitations in utilizing AI technology as a supporting tool for developing innovative and contextual learning media. This community service activity aims to provide training and mentoring to teachers in developing AI-assisted learning media through coding learning. The implementation method includes identifying partner needs, designing AI-based training materials, implementing training and mentoring directly, and evaluating the activity through observation and participant response questionnaires. The results of the activity show an increase in teachers' understanding and skills in utilizing AI for developing learning media, increased active participation during the training, and a positive response to the use of AI as an interactive and applicable learning medium. This activity has a positive impact on improving teachers' digital competence and becomes an alternative solution for developing innovative learning that can be implemented sustainably in educational environments.